Students' Perspective on Educational Delivery of Medical Laboratory Science Programs During COVID-19. - Nunez, Guillermo (Journal of Allied Health)
Issue: The COVID-19 pandemic altered the academic environment and led to significant changes in program delivery. Traditional classroom teaching was substituted with online instruction and laboratory simulations. Clinical laboratory practicums and classroom interactions are essential in the academic and professional training of Medical Laboratory Science students (MLS). It is important to address challenges caused by COVID-19 that affect students' educational experience. Method: The purpose is to evaluate the student's perspective on the impact of COVID-19 in relationship to the quality of program delivery. The mode value of the Likert scale on the impact of COVID-19 and the teaching quality of online learning were evaluated. Outcomes: The Likert scale was used to evaluate students' perspectives as it relates to challenges caused by COVID-19. Questions evaluate challenges, performance, and satisfaction during the pandemic. Conclusion: COVID-19 brought many challenges to educational systems globally. This study reveals how students can bridge the gap between traditional and online learning methods and create opportunities for implementing new, more effective models of delivery.